2019
DOI: 10.1093/jn/nxy233
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of Vitamin B-12 from Dairy Food, Meat, and Fish and Shellfish Are Independently and Positively Associated with Vitamin B-12 Biomarker Status in Pregnant Dutch Women

Abstract: Background The effect of vitamin B-12 from different animal foods on vitamin B-12 biomarker status has not previously been evaluated in pregnant women. Objective We examined the association of vitamin B-12 intake from dairy, meat, fish (including shellfish), and eggs with circulating concentrations of vitamin B-12 biomarkers and with the presence of vitamin B-12 deficiency in 1266 pregnant women participating in the KOALA Bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Another study among Dutch women during late pregnancy showed that vitamin B 12 intake from dairy, meat and fish, but not eggs was independently associated with plasma concentrations of total vitamin B 12 in a dose response manner. Furthermore, the intake of these foods was also independently associated with reduced odds of vitamin B 12 deficiency [ 47 ]. One of the reasons for the discrepancy between previous studies and our study could be due to the variations in the amount of vitamin B 12 intake from various animal source foods.…”
Section: Discussionmentioning
confidence: 99%
“…Another study among Dutch women during late pregnancy showed that vitamin B 12 intake from dairy, meat and fish, but not eggs was independently associated with plasma concentrations of total vitamin B 12 in a dose response manner. Furthermore, the intake of these foods was also independently associated with reduced odds of vitamin B 12 deficiency [ 47 ]. One of the reasons for the discrepancy between previous studies and our study could be due to the variations in the amount of vitamin B 12 intake from various animal source foods.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the effectiveness of healthy dietary patterns and components for the prevention of CVD and other diseases [ 2 , 3 , 4 ]. Fish is rich in various nutrients (e.g., protein, vitamin D and polyunsaturated fatty acids) and may have a beneficial role in preventing CVD events [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strict vegan or vegetarian diet without supplementation might lead to vB12D, already after 4 weeks of dietary change from omnivore to strict vegan diet [5,6]. In a study involving Dutch pregnant women (at 34-36 weeks of pregnancy) of mixed population including omnivore, lacto-ovo vegetarians and vegans, the main source of Cbl were dairy products, while eggs as Cbl source represented the minority of dietary Cbl source [7].…”
Section: From Uptake To Utilization 21 Chemistry and Dietary Sourcementioning
confidence: 99%